Old Well Management from Investment Law Perspective - Sang Ayu Putu Rahayu; Rahayu Fery Anitasari; Mia Pitaloka Krisna Putri; Anak Agung Ayu Diah Setyawati (Yuridika, 2023)
Upstream oil and gas business activities are exploration and exploitation activities carried out by cooperation contract contractors ( KKKS) in a work area with a cooperation contract, which in this case uses the type of PSC. In a working space, a part of the field is not cultivated by KKKS, which is commonly called an Old Well. Factually Old Well management regulations still need amendments and updates to developments, especially in upstream oil and gas contracts, which have now been switched to gross split PSC. This study adopted a normative method, with data sources drawn from primary and secondary legal materials. Ultimately, it is appropriate and reasonable to amend the management of Old Wells, considering that upstream business activities continue to develop and undergo changes. Therefore, understanding the old well management scheme, in line with regulatory changes in upstream oil and gas business activities, is essential. Furthermore, until now, what is still used is the type of operating cooperation (KSO) for old well management, but basically, the appropriate cooperation contract model to be used in the direction of Old Wells that can meet the needs of all parties involved in the type of profit-sharing contract, while still meeting the minimum clause requirements that must be in the Old Well management contract following the operational procedure guidelines (PTK) for the management of Old Wells. In this regard, the government should consider using a gross split production-sharing contract (PSC) scheme to manage oil and gas wells in Old Wells.